Sedimentological and petrographical investigations of the Early Triassic Vardebukta Formation on western Spitsbergen - Solvang, Ole-Marius Hafstad (The University of Bergen, 2017)
The earliest Triassic Barents Sea Basin received sediments from three sedimentary systems. Of these, the Fennoscandian and the Uralian systems have been well studied highlighting their sedimentology, provenance, extent and reservoir parameters. Contrarily, the system originating from Greenland/Arctic Canada has received little attention and remains poorly constrained. This study has investigated the latter system by detailed sedimentological outcrop analysis of the Induan Vardebukta Formation on western Spitsbergen at Festningen, Selmaneset and Studentdalen. The composition and texture of collected sandstone samples have been investigated by thin section analysis, warranting a comparison to its synchronous deposits in the Barents Sea. Based on the sedimentological analysis, 6 facies associations are recognized; supratidal flats, tidal sandflats, tidally influenced channels, delta front deposits, offshore transition zone and prodelta deposits. These are interpreted to have been deposited in a mixed type delta as evidenced by the great variety of sedimentary processes, and the clear progradational signature. Furthermore, the depositional environment was characterized by extensive biogenic carbonate production with a storm and wave agitated shelf. Point counting of the sandstones reveals high mineralogical maturity whereas the textural observations do not, suggesting a short transport from a nearby sedimentary source area. Additionally, the sediments show evidence of deep burial prior to deposition expressed through the sutured grain shape and the relative abundance of quartzite grains. Also, a clear bimodal grain size distribution is found in one of the samples, implying that the Vardebukta Formation partially originates from two distinctive source areas. It is possible that the sudden influx of sediments in the Induan is linked to Late Paleozoic – Early Mesozoic tectonism, which at the time led to a general tectonic uplift of the uplands to the Barents Sea Basin. This was possibly due to the onset of rifting ...